Pelatihan Kader Dalam Peningkatan Cakupan ASI Ekslusif Melalui Kelompok Pendukung ASI - Rekawati Susilaningrum; Sukesi; Rekawati Susilaningrum (Health Community Engagement, 2022)
The Data and Information Center (Pusdatin) of the Ministry of Health in 2015 showed that exclusive breastfeeding coverage was only 54.3 percent of the 80 percent target. The 2013 Riskesdas showed that breastfeeding coverage in Indonesia had increased to 42% from 32% of the Riskesdas data, but was still below 50% of the total. targets set by WHO. Aim. Increasing the Coverage of Exclusive Breastfeeding through Breastfeeding Support Groups in Gundih Village, Gundih Community Health Center, Bubutan District, Surabaya City. After the training activities were carried out, the results showed that most of the characteristics of cadres aged > 35 years (80%) and 20-35 years old as much as 20%, with an average education of high school and cadre occupation of a housewife, 2) for cadre knowledge there was an increase after training on exclusive breastfeeding was conducted, 4) most of the cadres had skills on how to breastfeed properly, both during training (%) and counseling (100%). The rest are skilled enough and there are no cadres who have less skills. Suggestions for Increasing Exclusive Breastfeeding Coverage 1) It is necessary to monitor the health center on the results of cadres’ task achievements so that they are able to evaluate the work of cadres periodically. 2)There is a need for continuous guidance to cadres on exclusive breastfeeding and the skills that support it. 3) The need for giving rewards to cadres so that it will increase motivation in the implementation of KP-ASI. Should cooperate with elements of the community such as community leaders, PKK, youth organizations, etc. in order to provide support for the Exclusive Breastfeeding program with the puskesmas as the facilitator